2007
DOI: 10.1007/s11064-007-9360-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron: The Redox-active Center of Oxidative Stress in Alzheimer Disease

Abstract: Although iron is essential in maintaining the function of the central nervous system, it is a potent source of reactive oxygen species. Excessive iron accumulation occurs in many neurodegenerative diseases including Alzheimer disease (AD), Parkinson's disease, and Creutzfeldt-Jakob disease, raising the possibility that oxidative stress is intimately involved in the neurodegenerative process. AD in particular is associated with accumulation of numerous markers of oxidative stress; moreover, oxidative stress has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(107 citation statements)
references
References 78 publications
(67 reference statements)
1
102
0
1
Order By: Relevance
“…Although PM mass has conventionally been used for setting of legislative airborne PM concentration limits, it is possible that ultrafine particle size and number are of greater significance in terms of mortality (26) 10 for Mexico City of between ∼30 and 70 μg·m −3 ). The abundant combustion-derived magnetite particles found in airborne PM can range widely in size, from less than 5 nm to more than 1 μm (15-17, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Although PM mass has conventionally been used for setting of legislative airborne PM concentration limits, it is possible that ultrafine particle size and number are of greater significance in terms of mortality (26) 10 for Mexico City of between ∼30 and 70 μg·m −3 ). The abundant combustion-derived magnetite particles found in airborne PM can range widely in size, from less than 5 nm to more than 1 μm (15-17, 19).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, compelling evidence has demonstrated that several neurodegenerative disorders involving oxidative stress are associated with an increase in brain Fe 2ϩ levels during the onset and progression of the disease (28 -31). Specifically, iron accumulation has been shown in brain regions with clear signs of neurodegeneration (32,33). Recent studies have demonstrated that molecules with the ability to bind iron are effective in slowing disease progression in both AD models and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is known to play a central role in many pathologies as neurodegenerative (Castellani et al, 2007) and hepatocellular injury (Uchiyama et al, 2008). We observed an increase in plasma free iron (HamlaouiGasmi et al, 2011b) that could result from its extrusion from the kidney.…”
Section: Discussionmentioning
confidence: 62%